2010
DOI: 10.1128/jvi.00134-10
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Xenotropic Murine Leukemia Virus-Related Virus by APOBEC3 Proteins and Antiviral Drugs

Abstract: Xenotropic murine leukemia virus-related virus (XMRV), a gammaretrovirus, has been isolated from human prostate cancer tissue and from activated CD4؉ T cells and B cells of patients with chronic fatigue syndrome, suggesting an association between XMRV infection and these two diseases. Since APOBEC3G (A3G) and APOBEC3F (A3F), which are potent inhibitors of murine leukemia virus and Vif-deficient human immunodeficiency virus type 1 (HIV-1), are expressed in human CD4؉ T cells and B cells, we sought to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

24
92
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(120 citation statements)
references
References 70 publications
(100 reference statements)
24
92
4
Order By: Relevance
“…3), most likely a reflection of the passage of XMRV through human cells, which renders the virus less sensitive to human complement (24)(25)(26). These results, as well as other reports showing restriction of XMRV replication in human cells (27,28), suggest that an established MLV infection in humans is unlikely.…”
supporting
confidence: 56%
“…3), most likely a reflection of the passage of XMRV through human cells, which renders the virus less sensitive to human complement (24)(25)(26). These results, as well as other reports showing restriction of XMRV replication in human cells (27,28), suggest that an established MLV infection in humans is unlikely.…”
supporting
confidence: 56%
“…It is therefore substantially more similar to XMRV than to either the polytropic or modified polytropic MLV sequences previously reported by Lo et al (17). There is no evidence for hypermutation mediated by APOBEC proteins in the patient-derived sequences as might be expected during an infection, given the susceptibility of MLV to mutation by these proteins (23). Thus, these new patient-derived MLV sequences show tremendous variation from the parental CFS type 1 sequence and as such are extremely unlikely to have evolved from the CFS type 1 sequence.…”
mentioning
confidence: 71%
“…XMRV detection in a small percentage of samples from healthy controls suggested widespread infection (7,18,29). Controversy has since surrounded XMRV detection, partly because many laboratories have been unable to detect XMRV in patient samples (2, 5, 6, 8-11, 14, 16, 19-21, 28, 30, 35, 37, 40) and partly because an almost identical virus has been found infecting a common prostate cancer cell line called 22Rv1 (12,15,23). These data strongly suggest that XMRV in patient material is the result of DNA contamination from laboratory cell lines or mouse DNA.…”
mentioning
confidence: 99%
“…The authors of these studies have proposed that the in vivo susceptibility to XMRV cannot be determined by the Xpr1 receptor expression alone but that the ability of different cell types to either transactivate the XMRV viral promoter or to restrict virus replication define how efficient the virus can spread in certain tissues (11). Recent studies have also shown that XMRV infectivity can be limited by the presence of known host restriction factors to retroviral replication, such as the human APOBEC3 and tetherin proteins, as well as mouse APOBEC3, tetherin, and Fv1 proteins (11,28). It is noteworthy that a number of human cells, including breast cells have been shown to be susceptible to infection by the mouse mammary tumor virus (MMTV) (13,14), in spite of the fact that the human orthologue of the murine transferrin receptor 1 (Trf1), which is the known cellular receptor for MMTV, is not able to support viral entry in human cells (32).…”
Section: Discussionmentioning
confidence: 99%